Patient safety culture as a mediator between healthcare personnel's psychological empowerment and patient outcome - Sutanto, Eldaa Prisca Refianti; Antonio, Ferdi; Massie, Roy G.A. (International Journal of Public Health Science (IJPHS), 2024)
Preventing healthcare errors and reducing damage are becoming the basic concepts of patient safety development. Healthcare personnel need to be more careful and minimize complications that can occur during patient care. Psychological empowerment is important to support a safety culture and patient outcomes. This study investigates the relationship between psychological empowerment (PE) and patient outcome (PO) mediated by patient safety culture (PSC). A cross-sectional survey study was conducted in private hospitals accredited by Joint Commission International. A total of 150 healthcare personnel as participants who met the requirements were obtained by distributing the questionnaires in March 2023. Significant results in mediating patient safety culture have been analyzed using partial least square-structural equation modeling (SEM). The dimensionality of PE and PSC was assessed by a new method that is a disjoint two-stage approach. The role of PSC was found to fully mediate the positive relationship between psychological empowerment and patient outcome (=0.436, p-value 0.05). This study contributes to growing the value of developing a safety culture and the function of psychological empowerment in healthcare staff to enhance patient outcomes.